2002
DOI: 10.1080/10575630290031981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Ultraviolet Light Absorbers on Photo-Stabilization of Azadirachtin-A

Abstract: The effect of photo-stabilization of Azadirachtin-A (Aza-A) was examined when exposed to sunlight and ultraviolet light in the presence of four structurally different ultraviolet stabilizers namely 4-aminobenzoic acid, 2,4-dihydroxybenzophenone, 4,4'-dihydroxybenzophenone and phenyl salicylate. The percentages of Aza-A recovered at different time intervals from slides exposed to different light conditions with and without UV stabilizers as well as kinetic studies indicated that the addition of phenyl salicylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[10][11][12][13] In this study, five natural innocuous UV light absorbers, namely ferulic acid, gallic acid, caffeic acid, cumaric acid and aloin from botanic resource were selected. These natural UV light absorbers can strongly absorb broad spectrum UV light.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In this study, five natural innocuous UV light absorbers, namely ferulic acid, gallic acid, caffeic acid, cumaric acid and aloin from botanic resource were selected. These natural UV light absorbers can strongly absorb broad spectrum UV light.…”
Section: Introductionmentioning
confidence: 99%
“…Photodegradation of pesticides in various phases has been comprehensively studied by several groups. (Maliakal et al 2002; McGarry et al 1997; Klopffer 1977; Franko et al 2005; Katagi 2004; Ishaque et al 2013; Eyheraguibel et al 2010; Trivella and Richard 2014; Nguyen et al 2012b; Nguyen et al 2012a; Cohen et al 2001; El-Nahhal et al 2001; Margulies et al 1987;Deota et al 2002) Earlier we reported that phenyl salicylate provides e cient photoprotection of azadirachtin, a neem-based biopesticide, which nds an important place in integrated pest management (IPM), in thin-lm as well as in solution (Fig.3) (Deota et al 2002;Deota et al 2003). Recently we reported effective photostabilization of chlorpyrifos by dialkoxy benzil derivatives (Fig.4) (Patel et al 2019).…”
mentioning
confidence: 99%